Physical vapor deposition of Bi2S3 as absorber material in thin film photovoltaics - Ten Haaf, Sebastian; Straeter, Hendrik; Brueggemann, Rudolf; Bauer, Gottfried H.; Felser, Claudia; Jakob, Gerhard (Thin Solid Films, 2013)
In order to investigate alternative absorber materials for inorganic solar cells, thin films of bismuth trisulfide (Bi2S3) were deposited under high vacuum conditions by the thermal evaporation method from compound material. The effects of the substrate temperature during deposition on the structural, stoichiometric, optical and electrical properties were investigated. Polycrystalline thin films close to an ideal stoichiometry could be deposited for temperatures TSub = 80-290 C; thereby a transition from rough needle-shaped particles with (hk0)-orientation parallel to the surface of the substrate towards block shaped grains with a preferred direction out of the surface could be observed. Confocal photoluminescence measurements revealed an optical pseudo band-gap of 1.32-1.36 eV and additionally a homogeneous lateral dependence in the optical properties of the thin films. By in-plane transport measurements, an increase of the conductivity was observed from 2 × 10- 7Ω- 1 cm- 1 for amorphous/microcrystalline films up to 2.5-8.5 × 10 - 3Ω- 1 cm- 1 for polycrystalline films deposited above 250 C. © 2012 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bi; Semiconductor; Solar cell absorber; Thin films